2011
DOI: 10.1111/j.1537-2995.2011.03077.x
|View full text |Cite
|
Sign up to set email alerts
|

Placenta perfusion has hematopoietic and mesenchymal progenitor stem cell potential

Abstract: Traditionally discarded after childbirth, the term placenta now appears to be an easily accessible and abundant source of diverse origin stem cells suitable for banking strategies and for future clinical applications, including adult therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Human stem cells represent a large reservoir of anti-apoptotic and antineoangiogenic growth factors, and there is growing interest in the ophthalmologic field regarding the use of human stem cells in the management of a group of retinal diseases 1 , 2 induced and supported by apoptotic and neoangiogenic mechanisms and mediated by proinflammatory growth factors, such as cytokines, chemokines, and vascular endothelial growth factor. In this study, we used placental human stem cells given that the placenta, 3 specifically the amniotic membrane, 4 represents an important source of human stem cells because of the abundance of cells which can be recovered and also the absence of ethical issues, considering that the placenta is a waste product. 5 Histological study of placental tissue has shown that the amniotic membrane is made up of a layer of amniotic epithelial cells resting on a basal membrane and, more externally, on a stroma of connective tissue or amniotic mesoderm in which there are amnion mesenchymal stromal stem cells.…”
Section: Introductionmentioning
confidence: 99%
“…Human stem cells represent a large reservoir of anti-apoptotic and antineoangiogenic growth factors, and there is growing interest in the ophthalmologic field regarding the use of human stem cells in the management of a group of retinal diseases 1 , 2 induced and supported by apoptotic and neoangiogenic mechanisms and mediated by proinflammatory growth factors, such as cytokines, chemokines, and vascular endothelial growth factor. In this study, we used placental human stem cells given that the placenta, 3 specifically the amniotic membrane, 4 represents an important source of human stem cells because of the abundance of cells which can be recovered and also the absence of ethical issues, considering that the placenta is a waste product. 5 Histological study of placental tissue has shown that the amniotic membrane is made up of a layer of amniotic epithelial cells resting on a basal membrane and, more externally, on a stroma of connective tissue or amniotic mesoderm in which there are amnion mesenchymal stromal stem cells.…”
Section: Introductionmentioning
confidence: 99%
“…The first step is the isolation of stem cells from a source. For the purpose of banking or clinical application, stem cells can be isolated from a variety of sources including umbilical cord (Can and Balci, 2011;Zhang et al, 2011), adipose tissuederived stem cells (Insausti et al, 2011;Zachar et al, 2011), peripheral blood stem cells (Kolbe et al, 2010;Hofmann et al, 2009), amniotic and placental stem cells (Klein and Fauza, 2011;Tsagias et al, 2011), dental pulp stem cells (Gronthos et al, 2011;Tirino et al, 2011), olfactory stem cells (Chen et al, 2006;Viktorov et al, 2008), and even human limbal epithelial stem cells (Vasania et al, 2011).…”
Section: Introductionmentioning
confidence: 99%